"It Is Truly a Struggle to Survive": The Hardships of Living on Low Wages. Issue 3 (July 2020) - Wexler, Sandra; Engel, Rafael J.; Steiner, Elizabeth; Petracchi, Helen
Many low-wage workers struggle to make ends meet despite working full-time. Surveys find that they confront material, financial, and medical hardships. This article presents hospital workers' descriptions of living on low wages, giving voice to their fears and challenges. These workers ( N = 156) testified to a city council-created Wage Review Committee, which posted the testimonies online. We qualitatively content-analyzed the testimonies to identify and describe their struggles. Hospital workers' testimonies brought depth and new understanding to arguments for raising wages. Low-wage workers can be effective advocates for their own interests.